Evaluasi Jaringan Tegangan Menengah Pasca Bencana Di Kabupaten Halmahera Selatan - Rasyid, Ramly (Department of Electrical Engineering, University of Patria Artha, 2020)
This study looked at the condition of power loss and falling voltage after the evaluation of the medium voltage network 20 kV after the earthquake disaster in South Halmahera district, especially in labuha extension on Bacan island The method used in this study is a quantitative research method with data collection done which is then simulated using ETAP 12.6 software. The simulation result obtained total power loss at Labuha extension is 44.3 kW + 66.8 kVAR or 80,154 kVA of 2,445 MVA delivery power, while the presentation of power loss is 3.278%, this is still considered feasible because the power loss on the medium voltage network 20 kV is 10% while in Labuha turtles the power loss is less than 10%. While the large fall in voltage at the largest Labuha extension at the Belang-Belang distribution substation is 3.96% or 792 volts, this is due to the channel length and presentation of the load reaching 83% against the distribution tranformator and the fall in the average voltage of Labuha's purgator is 3.025% or 605 volts against the nominal voltage of 20 kV. It is still considered viable for operation due to the permitted voltage fall on the 20 kV medium voltage network which is 5%.